A study of factors that influence financial stress among the workers at Holiday Villa & Suites Kota Bharu, Malaysia / Anis Fatimah Ilias - Ilias, Anis Fatimah (2015)
This study attempts to determine the factors influence financial stress among the workers at Holiday Villa Hotel & Suites Kota Bharu, Malaysia whether flood, debt levels, saving rates and financial education. This study was used 100 sample size among employees at Holiday Villa Hotel & Suites Kota Bharu, Malaysia (HVKB). The data collected was then tested on the linear regression analysis and then were use to test the hypothesis in this study. From the regression that were use in this study, researcher found that debt levels and saving rates are significant relationship with financial stress. While, flood and financial education show positive relationship with financial stress and there is no significant relationship between them. From this research, it revealed what is the most influence factors for the financial stress among employees at Holiday Villa Hotel & Suites Kota Bharu, Malaysia which is debt levels. Researcher also suggest some recommendation to the existing employees and future employees as well as for the future researcher